2020
DOI: 10.48550/arxiv.2005.04040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Turbulent flame speed and reaction layer thickening in premixed jet flames at constant Karlovitz and increasing Reynolds numbers

Abstract: A series of Direct Numerical Simulations (DNS) of lean methane/air flames was conducted in order to investigate the enhancement of the turbulent flame speed and modifications to the reaction layer structure associated with the systematic increase of the integral scale of turbulence l while the Karlovitz number and the Kolmogorov scale are kept constant. Four turbulent slot jet flames are simulated at increasing Reynolds number and up to Re ≈ 22000, defined based on the bulk velocity, slot width, and the reacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…In contrast to a large number of studies in the literature, where S T /S L has been sought to correlate with either u /S L or non-dimensional numbers including Re, Da, or Ka, the current result indicates that S T /S L and A T /A L strongly correlate and proportionally increase with the integral length scale. This is consistent with the previous work by Luca et al [20] and Attili et al [21] for a slot jet flame configuration in that S T /S L is proportional to l T /δ L . In fact, Luca et al [20] reported that the stretch factor was nearly unity in a global sense, while from a local perspective, Attili et al [21] suggested that the slight increase of the local I 0 with local l T /δ L involves an extra factor in enhancing the turbulent flame speed, which is the inner layer thickening.…”
Section: Turbulent Flame Speedsupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast to a large number of studies in the literature, where S T /S L has been sought to correlate with either u /S L or non-dimensional numbers including Re, Da, or Ka, the current result indicates that S T /S L and A T /A L strongly correlate and proportionally increase with the integral length scale. This is consistent with the previous work by Luca et al [20] and Attili et al [21] for a slot jet flame configuration in that S T /S L is proportional to l T /δ L . In fact, Luca et al [20] reported that the stretch factor was nearly unity in a global sense, while from a local perspective, Attili et al [21] suggested that the slight increase of the local I 0 with local l T /δ L involves an extra factor in enhancing the turbulent flame speed, which is the inner layer thickening.…”
Section: Turbulent Flame Speedsupporting
confidence: 93%
“…This is consistent with the previous work by Luca et al [20] and Attili et al [21] for a slot jet flame configuration in that S T /S L is proportional to l T /δ L . In fact, Luca et al [20] reported that the stretch factor was nearly unity in a global sense, while from a local perspective, Attili et al [21] suggested that the slight increase of the local I 0 with local l T /δ L involves an extra factor in enhancing the turbulent flame speed, which is the inner layer thickening. A stretch factor of nearly unity was also reported by Lapointe [42] based on DNS data of a turbulence-in-a-box configuration and by Kulkarni et al [41] for spherically expanding flames with different integral length scales.…”
Section: Turbulent Flame Speedsupporting
confidence: 93%
See 3 more Smart Citations